CITRA SASTRA DAN MORAL DALAM CERPEN BULAN OKTOBER PADA SURAT KABAR KEDAULATAN RAKYAT - Faizah, Inayah Isnaini; Yuliana, Wahyu; Setyawan, Arif (Bahtera Indonesia, 2025)
A short story is a work of fiction that usually focuses on an event, has a single plot, and has a relatively short and limited time scope. This research aims to describe the intrinsic structure and manifestation of moral values ​​in the short story October on Kedaulatan Rakyat. The research method for this study is descriptive qualitative. The data collection technique for this research uses reading and note-taking techniques for short stories. The steps for collecting data are by reading the short story carefully, recording appropriate data, identifying and clarifying the data. This research study is a structural study that focuses on the harmony between the intrinsic elements of short stories. The results of this research are (1) divine moral values, (2) individual moral values, and (3) social moral values. These three values ​​consist of positive and negative moral values. All actions that are based on religious and social norms are positive values, while behavior based on one's own will is a negative value.